2008
DOI: 10.1088/0004-637x/690/2/l93
|View full text |Cite
|
Sign up to set email alerts
|

First Detection of Glycolaldehyde Outside the Galactic Center

Abstract: Glycolaldehyde is the simplest of the monosaccharide sugars and is directly linked to the origin of life. We report on the detection of glycolaldehyde (CH 2 OHCHO) towards the hot molecular core G31.41+0.31 through IRAM PdBI observations at 1.4, 2.1, and 2.9 mm. The CH 2 OHCHO emission comes from the hottest (≥ 300 K) and densest (≥2×10 8 cm −3 ) region closest (≤ 10 4 AU) to the (proto)stars. The comparison of data with gas-grain chemical models of hot cores suggests for G31.41+0.31 an age of a few 10 5 yr. W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
102
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 132 publications
(107 citation statements)
references
References 17 publications
5
102
0
Order By: Relevance
“…This important organic molecule was first tentatively detected at 1.4 mm with the PdBI outside the Galactic centre, where it was observed in Sgr B2(N) (Hollis et al 2000) towards three massive hotcores (G31, G24A1, and G24A2) by Beltrán et al (2005). Later on, Beltrán et al (2009) confirmed the detection by observing two additional Glycolaldehyde transitions towards G31 at 2.1 and 2.9 mm with the PdBI. Recently, Jørgensen et al (2012) have detected 13 transitions towards the Class 0 IRAS 16293-2422 object at 0.4 and 1.4 mm, using the ALMA array towards the hot-corino surrounding the Solar-type protostar.…”
Section: Glycolaldehyde (Ch2(oh)cho)mentioning
confidence: 68%
“…This important organic molecule was first tentatively detected at 1.4 mm with the PdBI outside the Galactic centre, where it was observed in Sgr B2(N) (Hollis et al 2000) towards three massive hotcores (G31, G24A1, and G24A2) by Beltrán et al (2005). Later on, Beltrán et al (2009) confirmed the detection by observing two additional Glycolaldehyde transitions towards G31 at 2.1 and 2.9 mm with the PdBI. Recently, Jørgensen et al (2012) have detected 13 transitions towards the Class 0 IRAS 16293-2422 object at 0.4 and 1.4 mm, using the ALMA array towards the hot-corino surrounding the Solar-type protostar.…”
Section: Glycolaldehyde (Ch2(oh)cho)mentioning
confidence: 68%
“…Line profiles look like a rotating toroid with infall motion. Several complex hot-core molecules have been observed in G31, including glycolaldehyde CH 2 OHCHO (Beltrán et al 2009), but again no abundance ratios have been presented.…”
Section: Iras 18089-1732mentioning
confidence: 99%
“…It has been detected in the SFR Sgr B2(N) by Hollis et al (2000) from 2 and 3 mm single-dish surveys, with an estimated rotational temperature (T rot ) of 35 K from 34 lines detected. Beltrán et al (2009) reported identification of three lines towards the hot core G31.41 +0.31 using the Plateau de Bure Interferometer. Their analysis indicated that emission comes from the hottest (≥300 K) and the densest (≥2 × 10 8 cm −3 ) region closest to the protostar.…”
Section: Introductionmentioning
confidence: 99%